2021
DOI: 10.1101/2021.06.04.447101
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimental depletion of gut microbiota diversity reduces host thermal tolerance and fitness under heat stress in a vertebrate ectotherm

Abstract: Predicting the responses of ectotherms to climate change is a global conservation priority which requires identifying factors that influence how animals respond physiologically to changing temperature. Host-associated microbial communities impact animal physiology and have been shown to influence host thermal tolerance in invertebrate systems. However, the role of commensal microbiota in thermal tolerance of ectothermic vertebrates is unknown. Here we show that experimentally depleting the diversity of the tad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 132 publications
(184 reference statements)
0
3
0
Order By: Relevance
“…Heat acclimation experiments in both ectotherm and endotherm hosts have shown that variations in environmental temperature significantly affect the gut microbial community ( 9 , 24 26 ). In this study, we used high-throughput 16S rRNA gene sequencing to investigate the impact of microhabitat temperature variations on gut microbial composition and diversity in R. pusillus .…”
Section: Discussionmentioning
confidence: 99%
“…Heat acclimation experiments in both ectotherm and endotherm hosts have shown that variations in environmental temperature significantly affect the gut microbial community ( 9 , 24 26 ). In this study, we used high-throughput 16S rRNA gene sequencing to investigate the impact of microhabitat temperature variations on gut microbial composition and diversity in R. pusillus .…”
Section: Discussionmentioning
confidence: 99%
“…Dr. Kevin Kohl showed that microbial communities contributed to host thermal tolerance in tadpoles subjected to temperature increase. 7 In wild Anolis lizards, short-term climate warming does not have a significant effect on the gut microbiome whereas sustained drought does, as explained in Claire E. Williams's poster (University of Nevada, USA). In addition to climate change, pollutants and radiation exposure can also impact wild animals gut microbiome as illustrated by Dr. Diana Lafferty (Northern Michigan University, USA) working on wild boars in the Fukushima difficult-to-return zone, and Sameli Piirto (University of Jyväskylä, Finland) whose PhD project will investigate the effects of radionuclides exposure on great tits in Chernobyl (Ukraine).…”
Section: Talks and Postersmentioning
confidence: 99%
“…External factors also shape an individual's microbiome with consequences on host fitness, especially in the face of anthropogenic perturbations. Dr. Kevin Kohl showed that microbial communities contributed to host thermal tolerance in tadpoles subjected to temperature increase 7 . In wild Anolis lizards, short‐term climate warming does not have a significant effect on the gut microbiome whereas sustained drought does, as explained in Claire E. Williams's poster (University of Nevada, USA).…”
Section: Talks and Postersmentioning
confidence: 99%